The Death of Governor Andrés González Muñoz and the Rise of Autonomy in Puerto Rico - Berry-Cabán, Cristóbal S. (International Journal of Culture and History, 2024)
Puerto Rico’s road toward autonomy with Spain had been a long-sought goal. On January 11, 1898, General Andrés González Muñoz arrived in San Juan, Puerto Rico to assume governorship of the island and implement autonomy, a new form of government which gave the island the right of self-rule. This article provides an overview of the rise of autonomy and the important role played by González Muñoz in implementing it. Spain fought hard to keep its last remaining American colonies under its orb granting Puerto Rico and Cuba limited freedom and rights. González Muñoz who had played a role in ensuring that these American colonies would remain under Spain was tasked with ensuring its implementation. Upon his arrival, he attended required ceremonial duties. However, before the day was over, he had died. González Muñoz death contributed to the political uncertainty that would haunt Puerto Rico throughout 1898.